37th Joint Propulsion Conference and Exhibit 2001
DOI: 10.2514/6.2001-3646
|View full text |Cite
|
Sign up to set email alerts
|

Micropropulsion system selection for precision formation flying satellites

Abstract: Several upcoming scientific interferometry missions (ST-3, LISA, TPF, MAXIM and SPECS) will push the limits of precision positioning of satellites. These spacecraft will require position and attitude control actuation on exceedingly small scales, which has not previously been performed. The several candidate propulsion systems for these missions include: colloid thrusters, field emission electrostatic propulsion thrusters (FEEP), pulsed plasma thrusters (PPT) and miniature cold gas thrusters. In order to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…4 The study compared the different micropropulsion systems for the purpose of station keeping by implementing them in representative control strategies to evaluate the propellant usage. The overall system mass and cost were compared and included an estimate of the cost of bringing each type of propulsion system from its current technology readiness level (TRL) up to TRL 8.…”
Section: Tpf Comparisonsmentioning
confidence: 99%
“…4 The study compared the different micropropulsion systems for the purpose of station keeping by implementing them in representative control strategies to evaluate the propellant usage. The overall system mass and cost were compared and included an estimate of the cost of bringing each type of propulsion system from its current technology readiness level (TRL) up to TRL 8.…”
Section: Tpf Comparisonsmentioning
confidence: 99%
“…The various approaches, all of which tend to have their unique benefits, have included liquid/solid chemical propellants and electric propulsion concepts, with somewhat of a focus on the latter. For the interested reader, a comprehensive survey of micropropulsion concepts under development can be found in Mueller (2000) and a review of micropropulsion systems targeted for formation flying applications can be found in Reichbach et al (2001). In assessing the relative merit of a given approach, it is important to recognise that each mission specification will have its own set of unique constraints.…”
Section: Brief Overview Of Micropropulsion Conceptsmentioning
confidence: 99%
“…Microthrusters operating on a variety of propellants provide motion power for main propulsion and attitude or orbit control to microsatellites or micro unmanned air vehicles (UAVs) [1]. A microthruster using solid propellants has a number of advantages, such as flexibility in propellants, easy size enlargement or reduction, no need for fuel tank/tubing or valves, and no leakage problems.…”
Section: Introductionmentioning
confidence: 99%